2017
DOI: 10.1186/s12933-017-0571-1
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase inhibitor miglitol attenuates glucose fluctuation, heart rate variability and sympathetic activity in patients with type 2 diabetes and acute coronary syndrome: a multicenter randomized controlled (MACS) study

Abstract: BackgroundLittle is known about clinical associations between glucose fluctuations including hypoglycemia, heart rate variability (HRV), and the activity of the sympathetic nervous system (SNS) in patients with acute phase of acute coronary syndrome (ACS). This pilot study aimed to evaluate the short-term effects of glucose fluctuations on HRV and SNS activity in type 2 diabetes mellitus (T2DM) patients with recent ACS. We also examined the effect of suppressing glucose fluctuations with miglitol on these vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Recent investigations have demonstrated that glucagon-like peptide-1 (GLP-1) analogue inhibits oxidative injuries in vascular endothelial cells [ 28 ]. Another study suggested that the α-glucosidase inhibitor attenuated GV, heart rate variability, and sympathetic activity in ACS patients with type 2 DM [ 29 ]. According to the current study’s results, we emphasize that there is a possibility of improving prognosis by reducing GV via the use of CGM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have demonstrated that glucagon-like peptide-1 (GLP-1) analogue inhibits oxidative injuries in vascular endothelial cells [ 28 ]. Another study suggested that the α-glucosidase inhibitor attenuated GV, heart rate variability, and sympathetic activity in ACS patients with type 2 DM [ 29 ]. According to the current study’s results, we emphasize that there is a possibility of improving prognosis by reducing GV via the use of CGM.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we found that despite of significant decreased FBG by DPP4 inhibitors compared with AGIs, treatment with DPP4 inhibitors also significantly decreased PPG as compared with AGIs in T2DM patients, which is not reported in previous meta-analysis (Cai et al, 2015). This is of clinical significance since AGIs are often considered as the OADs of choice to lower PPG because of its direct pharmacological action, which is to inhibit the absorption of carbohydrates during the meals (Liu and Ma, 2017; Shimabukuro et al, 2017). Based on our results, DPP4 inhibitors should be considered in patients with high PPG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Serum average and variability of glycated albumin level, which represent the short-term (2–3 weeks) glycemic status, are significantly associated with the presence of CAN [ 20 ]. Shimabukuro et al demonstrated that short-term suppression of glycemic variability with α-glucosidase inhibitor can improve sympathetic nervous system activity and modify heart rate variability [ 21 ]. Jaiswal et al found that the prevalence of CAN in a young diabetes cohort was comparable to that reported in the adult diabetes population and that elevated triglyceride levels were the modifiable factors associated with CAN in this group [ 22 ].…”
Section: Discussionmentioning
confidence: 99%